Role of Social Media influence on Customers Impulsive Buying Behaviour towards Apparel - S. Sudha; Bharathi Karuppiah (International Journal of Supply Chain Management, 2018)
The purpose of this research is to study the association between Social Media factors towards Impulsive Buying Behavior of apparel among the customers in Chennai city. The are three important Social Media feature are being acknowledged like (Media Entertainment, Social Interaction ,Word of mouth ) which are endogenous variables in the study and the customer impulsive buying behavior as a exogenous variable. Each of the Social Media factors was tested using SPSS software .The test comprises of cronbach alpha, SEM. The test help us to understand the consumers response towards the Social Media factors. Non-Probability sampling technique was implemented for the collection of data. A consistent questionnaire was used in the study .It was circulated among 230 respondents 194 responses was received back 92%was the response rate of the study . Key words: Customers, Impulsive Buying Behavior, Social Media, Word of mouth, Social Interaction, Media Entertainment